2011
DOI: 10.1007/s00125-011-2184-7
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed subjective sleep characteristics in adult patients with long-standing type 1 diabetes mellitus

Abstract: Aims/hypothesisDecreased sleep duration and/or impaired sleep quality negatively influence glucoregulation. The aim of this study was to assess subjective sleep characteristics in patients with type 1 diabetes, to relate sleep characteristics to long-term glycaemic control and to assess possible risk factors for impaired sleep.MethodsWe studied 99 adult patients with type 1 diabetes (55 men, 44 women, duration of diabetes 26.9 ± 1.2 years) and 99 age-, sex- and BMI-matched non-diabetic controls. Subjective sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
6
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 36 publications
9
79
6
2
Order By: Relevance
“…In addition, worse sleep quality was previously reported in individuals with T1DM (13,14), which we did not observe in the present study. In Jauch-Chara and cols.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In addition, worse sleep quality was previously reported in individuals with T1DM (13,14), which we did not observe in the present study. In Jauch-Chara and cols.…”
Section: Discussioncontrasting
confidence: 76%
“…The absence of correlation between sleep duration and glycemic control was not surprising, since other groups have reported similar results before (10,14). In our study, differently from findings of other groups that studied T1DM children and adolescents (10,12), and in accordance with a study with T1DM adults (14), sleep duration was not different between T1DM and control subjects.…”
Section: Actimetersupporting
confidence: 83%
See 1 more Smart Citation
“…Previous reports demonstrated abnormal sleep pattern in T1DM population (van Dijk et al, 2011;Perfect et al, 2012). Electrographical changes in brain activity during sleep in association with hyperglycemic excursions, as we present in our study, may underlie these abnormalities.…”
Section: Changes Associated With Hyperglycemia During Sleepcontrasting
confidence: 36%
“…Because PSG studies have identified poor sleep quality 9,10 and altered sleep architecture in individuals with T1DM, 11,12 it is important for ongoing research to determine if actigraphy provides a valid measure of sleep in individuals with T1DM. The aim of this investigation was to compare Actiwatch2-and PSG-based measures of sleep in young adults with T1DM, and to determine which threshold setting provides the best correspondence.…”
Section: Validity Of Actigraphy In Measurement Of Sleep In Young Adulmentioning
confidence: 99%